Representation of Human in the Album "Manusia" by Tulus (Semiotic Analysis of Ferdinand De Saussure) - Sugiarti, Lilian (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
Human life's journey, an endless exploration, unfolds continuously throughout existence. Like a flowing melody, this journey encompasses stages that depict the dynamics of human existence. This study focuses on Tulus' album 'Manusia,' an artistic creation providing a profound portrayal of diverse human experiences. Employing Ferdinand De Saussure's semiotic approach, this research delves into the symbolic meanings embedded within song lyrics. The album transcends mere melodies and words, reflecting the intricacies of humanity, ranging from love and loss to hope. A descriptive qualitative method is utilized to unveil concealed meanings behind the words. The research results illuminate how the album represents human relationships with their environment. Its lyrics depict human interaction with the surrounding world, presenting concepts of existence and reflection. 'Manusia' becomes an artistic expression capable of unraveling the inner complexities of humanity, giving voice to emotions often challenging to articulate in ordinary words.